DIRECTIVE SPEECH ACTS AND GENDER-BASED LANGUAGE PATTERNS IN THE COMMENT SECTION OF THE @MENKEURI INSTAGRAM ACCOUNT - Indah Sari; Fatmawati (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2026)
This study examines directive speech acts and gender-based language patterns in the comment section of the official Instagram account @menkeuri on the post entitled “Solid Economic Growth, Acceleration of Spending Continues to Be Boosted.” The study aims to identify the forms and functions of directive speech acts and to analyze gender differences in their use within the context of digital political communication. This research employed a descriptive qualitative approach with a content analysis method. The data consisted of comments containing directive speech acts posted within one month after the upload of the post. Data were collected through documentation and note-taking techniques and analyzed using Ibrahim’s (1992) classification of directive speech acts. The findings reveal 154 directive speech acts categorized into five forms: requestives (63.63%), questions (12.34%), requirements (11.04%), advisories (9.74%), and permissives (3.25%), while prohibitives were not found. The identified functions include requesting, pleading, praying, questioning, demanding, ordering, advising, warning, proposing, and suggesting, with praying emerging as the most dominant function. In terms of gender, male netizens produced more directive utterances than female netizens. Male language patterns tended to be more assertive and action-oriented, whereas female language patterns tended to emphasize empathy, solidarity, and politeness. These findings indicate that gender-related language patterns may influence how users express aspirations, criticism, and demands regarding public policy in digital political communication.